2011
DOI: 10.1007/s10897-011-9363-z
|View full text |Cite
|
Sign up to set email alerts
|

Shock, Adjust, Decide: Reproductive Decision Making in Cystic Fibrosis (CF) Carrier Couples—A Qualitative Study

Abstract: Cystic fibrosis (CF) is the most common recessive condition affecting the White British population. Facilitating reproductive decision making for couples at genetic risk for CF is an important aspect of genetic counseling practice in the UK. The purpose of this study was to explore the reproductive decision making process for 31 members of CF carrier couples (15 men and 16 women) with or without an affected child. The design involved a qualitative approach consisting of semi-structured interviews and data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…As reported by carriers in the current study and other studies, the initial phone call disclosing the test result elicits a level Letter from genetic service to family members (approach G) Useful 2 (10) Not useful 19 90of shock and is often recalled as a particularly stressful time (Myring et al 2011). Shock and anxiety may limit an individual's absorption and recollection of information discussed (McClaren et al 2013).…”
Section: Discussionmentioning
confidence: 55%
“…As reported by carriers in the current study and other studies, the initial phone call disclosing the test result elicits a level Letter from genetic service to family members (approach G) Useful 2 (10) Not useful 19 90of shock and is often recalled as a particularly stressful time (Myring et al 2011). Shock and anxiety may limit an individual's absorption and recollection of information discussed (McClaren et al 2013).…”
Section: Discussionmentioning
confidence: 55%
“…This finding also relates to other reproductive decision-making in other genetic contexts. For example, Myring and her colleagues (Myring et al 2011) found Cystic Fibrosis (CF) carrier couples who already had a child or pregnancy affected with CF were more likely to have another pregnancy, while CF carrier couples who had a healthy child first were less likely to consider another pregnancy because of their concern for the child's risk. Future research may consider comparing and contrasting several life-threatening genetic conditions about reproductive concerns.…”
Section: Discussionmentioning
confidence: 99%
“…In general, women have a variety of reproductive options including personal pregnancy, surrogacy, in-vitro fertilization, and adoption. Researchers have examined family planning and reproductive decision-making in a variety of different health contexts such as Huntington's Disease (Downing 2005;Klitzman et al 2007), Cystic Fibrosis (Myring et al 2011), Multiple Sclerosis (Alwan et al 2012), HIV/AIDS (Matthews et al 2013), and cancer (Chung et al 2013;Clayman et al 2013). Yet most of this scholarship focuses on reproductive decision-making process rather than the negotiation of personal health risk and reproductive concerns.…”
Section: Family Planning and Reproductive Decision-makingmentioning
confidence: 99%
“…A recent study describes reproductive decision making for CF carrier couples with and without an affected child; once relatives learn that they are carriers and if their partner is also a carrier, there are significant impacts both emotionally and practically for future (and existing) pregnancies. 13 Aside from reproductive planning, another reason for carrier testing is to clarify carrier status to pass information on to other relatives. This may particularly apply to grandparents of a child diagnosed with CF through NBS, and to great aunts/uncles who are in a similar stage of life to grandparents.…”
Section: Genetics In Medicinementioning
confidence: 99%